2010
DOI: 10.1016/j.chroma.2009.11.078
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency hydrophilic interaction chromatography by coupling 25cm×4.6mm ID×5μm silica columns and operation at 80°C

Abstract: Recently, hydrophilic interaction chromatography (HILIC) has emerged as a valuable orthogonal tool to reversed-phase liquid chromatography (RP-LC) as it allows for resolution of highly polar ionisable compounds. The relationships between separation efficiency, column length and speed of analysis for 4.6 mm ID x 5 µm silica particle columns in HILIC are demonstrated using kinetic plots. The kinetic plots constructed for conventional pressure systems operating at 350 bar and at 30 o C and 80°C are confirmed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Others have also reported effects on HILIC selectivity as function of organic solvent content, e.g. Jandera and coworkers who showed that the elution order under isocratic conditions may change as a function of the ACN mobile phase content [17], and Sandra and coworkers who observed that a gradient could increase the resolution of some compounds but decrease the resolution of others [18].…”
Section: Solvent Composition Adjustment For Improving Separationmentioning
confidence: 98%
See 1 more Smart Citation
“…Others have also reported effects on HILIC selectivity as function of organic solvent content, e.g. Jandera and coworkers who showed that the elution order under isocratic conditions may change as a function of the ACN mobile phase content [17], and Sandra and coworkers who observed that a gradient could increase the resolution of some compounds but decrease the resolution of others [18].…”
Section: Solvent Composition Adjustment For Improving Separationmentioning
confidence: 98%
“…4). An increase in temperature usually leads to a shift in the equilibrium towards the mobile phase, shortening the retention time [18,20]. Inverse relationships between temperature and retention has been found and studied mostly regarding RP phases, and has been related to e.g.…”
Section: Temperature As a Separation Parametermentioning
confidence: 99%
“…Johnsen and colleagues [34] also indicate higher efficiencies on the ZIC-p-HILIC column are obtained with high temperature and emphasize that the retention time also increases with the increase of temperature. Contrary to what occurs in RPLC, where the increase in temperature generally leads to a change in the equilibrium towards the mobile phase, which shortens the retention time [36,37]. It could be speculated that the temperature affects the hydration of the analytes to explain this behavior in polymeric zwitterionic columns, therefore affecting retention [38].…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows some examples of variable-length kinetic plots. Many other examples can be found in the literature. , Figure a,c displays the same data set, relating to two different sizes of a core-shell particle. Both plots clearly emphasize the complementary of both particle sizes, with the smaller particles performing best for short separations (small t 0 ), while the opposite holds in the range of separations requiring large times.…”
Section: Representation Modes Most Relevant For Column Usersmentioning
confidence: 98%